Techno-morphological analysis of furniture objects from the colonial period, La Quinta site, Punilla, Cordoba (Argentina) - Mendoza, Adrián Alejandro (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2022)
The present work comprises the result of the techno-morphological analysis carried out on a total of 650 copies of different types of furniture objects made with different raw materials, belonging to the Colonial period, located in a sector of the site called “La Quinta” (Punilla ), which can be found in the collection of museums and private collections in Córdoba. It is interesting as an objective to be able to determine through the study of material culture, mainly on a fragmentary register, which societies occupied that space and which type of function they fulfilled. The results obtained allow us to suggest that this archaeological site formed part of an encomienda made up of local indigenous groups and other regions, mainly from the NOA and the coast.